The role of eye camps in rural areas of Nepal - Gurung, J.; Tuladhar, S.; Sharma, A (Journal of Gandaki Medical College-Nepal, 2019)
Objective: To evaluate the role of eye camp in reducing avoidable blindness in Nepal.Methods: A cross sectional camp-based study was conducted in a remote village of Eastern Nepal, where a six days eye screening and free surgical camp was done.Results: A total of 467 people were screened, where 280 (60%) were males and 187 (40%) females. Mean age of the patient was 47.6 years. Age related cataract 165 (17.7%) was the commonest cause of decreased vision followed by refractive error 105 (11.2%). Among 165 cataract patients, 81 (49.1%) underwent cataract surgery. The mean age of the operated patient was 74.9 years. Among the operated eyes, visual impairment was present in 56 (69.1%) eyes and blindness in 25 (30.9%). After cataract surgery, visual acuity was restored to 6/6-6/18 in 58 (71.6%), 6/24-6/60 in 18 (22.2%) and five (6.2%) had visual acuity of